Respuesta :

Answer:

n= -3

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

4n+2=6(

1

3

n−

2

3

)

4n+2=(6)(

1

3

n)+(6)(

−2

3

)(Distribute)

4n+2=2n+−4

4n+2=2n−4

Step 2: Subtract 2n from both sides.

4n+2−2n=2n−4−2n

2n+2=−4

Step 3: Subtract 2 from both sides.

2n+2−2=−4−2

2n=−6

Step 4: Divide both sides by 2.

2n

2

=

−6

2

n=−3

Answer:

n = -3

Step-by-step explanation:

The first step you want to do is try to get rid of those parenthesis and to do that you want to distribute the 6 into 1/3n and 2/3 and you get

4n + 2 = [tex]\frac{6}{3}[/tex]n - [tex]\frac{12}{3}[/tex]

that can be simplified to

4n + 2 = 2n - 4

subtract 2n from both sides and you get

2n + 2 = -4

subtract 2 from both sides

2n = -6

divide both sides by 2 you get

n = -3